2008
DOI: 10.1021/jf0725225
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Yak (Bos grunniens) Cheese Including Conjugated Linoleic Acid and trans-18:1 Fatty Acids

Abstract: The esterified fatty acid composition of cheese (YC) from yak (Bos grunniens), reared in the highlands of the Nepalese Himalayas, was studied using capillary gas-liquid chromatography and compared with that of dairy cow Cheddar cheese (DC) purchased in a local market. The YC was collected from Dolakha, Nepal. The YC had a lower (P < 0.001) myristic acid (C14:0; 6.7 vs 10.3%, YC vs DC, respectively) and palmitic acid content (C16:0; 23.3 vs 29.2%, YC vs DC, respectively) compared to DC. The YC had a lower (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 54 publications
3
29
1
Order By: Relevance
“…These peptides are multifunctional bioactives with potential use for producing value-added functional foods and proteins [34]. Compared to cow milk fat, n-3 PUFA in yak milk fat is extremely higher (e.g., 3.2 times) [35]. The n-3 PUFA to n-6 PUFA ratio in yak cheese was 0.87, but only 0.20 in cow cheese.…”
Section: Yak Milk For Nutrition and Healthmentioning
confidence: 99%
“…These peptides are multifunctional bioactives with potential use for producing value-added functional foods and proteins [34]. Compared to cow milk fat, n-3 PUFA in yak milk fat is extremely higher (e.g., 3.2 times) [35]. The n-3 PUFA to n-6 PUFA ratio in yak cheese was 0.87, but only 0.20 in cow cheese.…”
Section: Yak Milk For Nutrition and Healthmentioning
confidence: 99%
“…According to a recent study, a VA:RA ratio of approximately 3:1 was observed in milk, butter, and cheese of cows on a modified diet to increase CLA in their milk . Somewhat lower VA:RA ratios were found in cheese from yak and cow (2.4:1 and 2.7:1, respectively), with expectedly higher amounts of both VA (2.27% versus 0.57% of FAME) and RA (6.23% versus 1.35%) in yak-derived cheese due to altitude and grass diversity (Or-Rashid et al, 2008). These results correspond to 4.0 and 4.6 times higher contents of VA and RA, respectively, in yak compared with cow cheese.…”
Section: Correlation Between Cla and Va In Food Sourcesmentioning
confidence: 88%
“…Animals in modern production systems are fed on silage and crop concentrate rather than pasture and this leads to a great reduction in CLA content in foods derived from these animals and consequently to lower CLA availability in human diets. It has been repeatedly shown that an animal-adapted feeding pattern, i.e., grazing for cows, not only increased CLA in meat and dairy products, but also mono-(MUFA), polyunsaturated (PUFA), n À 3 fatty acids, and VA content, while at the same time reduced saturated fatty acids (SFA) and increased the n À 6/n À 3 ratio substantially (Bisig et al, 2008;Couvreur, Hurtaud, Lopez, Delaby, & Peyraud, 2006;Dannenberger et al, 2004;Dewhurst, Shingfield, Lee, & Scollan, 2006;French et al, 2000;Garcia, Pensel, et al (2008); Hollo et al, 2005;Kraft, Kramer, Schoene, Chambers, & Jahreis, 2008;Or-Rashid, Odongo, Subedi, Karki, & McBride, 2008).…”
Section: Factors Influencing Cla and Va Content In Foodmentioning
confidence: 99%
“…Furthermore, the composition of yak milk is higher than that of Jersey and Holstein dairy cows. The total dry matter is around 17-18% during the main lactating period, fat content is around 6.5%, protein and lactose are each around 5.5%, and ash 0.8% (Or-Rashid et al, 2008). Concentrations of unsaturated fatty acid, such as conjugated linoleic acid (CLA), were greater than those of cow milk (OrRashid et al, 2008).…”
Section: Introductionmentioning
confidence: 99%